1975
DOI: 10.1524/ract.1975.22.4.180
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Behaviour of Some Actinides on Zirconium Phosphate from Mineral Acid-Alcohol Media

Abstract: The present work is an investigation of the adsorption behaviour of thorium, protactinium, uranium, neptunium and plutonium on zirconium phosphate from NH4CI, HCl and HCl-alcohol media. In mixtures of HCl with different alcohols, distribution coefficients were found to depend on both, the alcohol content and the acid concentration. The eifect of alcohol on the adsorption of the mentioned elements was found to Vary from one element to another. Results are discussed and conditions for interseparation of the ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1978
1978
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The adsorption behavior of protactinium on zirconium phosphate cation exchanger from ammonium chloride, hydrochloric acid, and hydrochloric acid-alcohol media has been investigated (Souka et al, 1975c). The distribution coefficients in solvent mixtures of hydrochloric acid and various alcohols depend on both alcohol content and acid concentration.…”
Section: Enrichment Of Aqueous Raffinatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorption behavior of protactinium on zirconium phosphate cation exchanger from ammonium chloride, hydrochloric acid, and hydrochloric acid-alcohol media has been investigated (Souka et al, 1975c). The distribution coefficients in solvent mixtures of hydrochloric acid and various alcohols depend on both alcohol content and acid concentration.…”
Section: Enrichment Of Aqueous Raffinatesmentioning
confidence: 99%
“…The extraction behavior of protactinium in mixtures of uranium, thorium, and neptunium with trilaurylamine from sulfonic acid solutions (Souka et al, 1975c) indicates low distribution coefficients at high acid concentrations; the addition of hydrochloric acid appreciably enhances extraction. The extraction of protactinium (V) with trioctylamine (TOA) dissolved in xylene from thiocyanate solutions containing uranium and thorium have been successfully accomplished (Nekrasova et al, 1975a); tracer amounts of Pa can exist in monomeric form in thiocyanate media for several months, but at Pa(V) concentrations greater than 10 -6 M, polymers form and the efficacy of TOA as an extractant is seriously impaired (Nekrasova et al, 1975b).…”
Section: (B) Ion Exchangementioning
confidence: 99%
“…Thus, KAKIHANA and KOJIMA [6] showed that in solutions of more than 30 mole % of ethanol, the selectivity coefficient of K + exchange on amorphous ZrP is, contrary to the aqueous medium, higher than that of Cs + exchange. Besides, some studies [7,8] have been done on the sorption of some elements on amorphous ZrP from mixed solvents with the main aim of obtaining better separation conditions. Ion exchange on crystalline ZrP is usually thermodynamically irreversible whereby hysteresis phenomena are often observed [2, 9 -14], and since it was intended to carry out a study, including the thermodynamic aspect of the behaviour of ZrP in mixed solvents, amorphous ZrP was chosen for the study.…”
Section: Introductionmentioning
confidence: 99%